2006
DOI: 10.3341/kjo.2006.20.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Antielevation Syndrome after Unilateral Anteriorization of the Inferior Oblique Muscle

Abstract: PurposeTo report antielevation syndrome with restriction of elevation on abduction in the operated eye and overaction (OA) of the inferior oblique muscle (IO) of the contralateral eye after unilateral IO anteriorization (AT).MethodsMedical records were reviewed retrospectively in 8 of 24 patients who underwent unilateral IOAT. Four patients were referred from other hospitals after the same surgery.ResultsFour patients had infantile esotropes. The rest showed accommodative esotropia, superior oblique palsy, exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 13 publications
2
19
0
1
Order By: Relevance
“… 1 , 5 , 12 , 15 The forced duction test is more positive in the adherence syndrome than in the anti-elevation, where only a slight resistance is found in the temporal superior direction. 7 Finally, the deviation progressively worsens in the adherence syndrome and may occur later than in the anti-elevation (earlier onset and a stable deviation). 16 In our series of 6 cases were all diagnosed of adherence syndrome because surgery performed on the inferior oblique had been variable [in one case (no.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 5 , 12 , 15 The forced duction test is more positive in the adherence syndrome than in the anti-elevation, where only a slight resistance is found in the temporal superior direction. 7 Finally, the deviation progressively worsens in the adherence syndrome and may occur later than in the anti-elevation (earlier onset and a stable deviation). 16 In our series of 6 cases were all diagnosed of adherence syndrome because surgery performed on the inferior oblique had been variable [in one case (no.…”
Section: Discussionmentioning
confidence: 99%
“…There are other situations following inferior oblique surgery causing limitation of elevation, such as the inferior oblique inclusion syndrome and the anti elevation syndrome. 3 , 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…Limiting surgery to the affected eye can risk uncovering a DVD in the fellow eye following unilateral surgery (Nabie et al 2007); this risk is reduced when a strong contralateral fixation preference is present (Bothun and Summers 2004) or VA in the affected eye is two or more lines lower than that of the other eye. Small but reportedly insignificant amounts of hypotropia may also occur in DVD (Bothun and Summers 2004) with some showing significant limitation of unilateral elevation (Cho et al 2006). Small but reportedly insignificant amounts of hypotropia may also occur in DVD (Bothun and Summers 2004) with some showing significant limitation of unilateral elevation (Cho et al 2006).…”
Section: Unilateral or Bilateral Dissociated Vertical Deviationmentioning
confidence: 98%
“…Mims and Wood (1989b) reported on a series of 61 children with inferior oblique overaction who underwent bilateral recession with antero-positioning procedures. If a truly unilateral DVD is present, then unilateral surgery has been recommended on the overacting inferior oblique muscle, but this may result in restricted elevation (Cho et al 2006) (antielevation syndrome). Kratz et al (1989) also reported on the effect of ATIO tendon in DVD.…”
Section: Dissociated Vertical Deviation With Overaction Of the Inferimentioning
confidence: 99%
“…Как и первичная, вторичная гиперфункция нижней косой мышцы проявляется отклонением глаза кверху в приведении, однако значительная гипертропия присутствует и в первичном положении взора. Кроме того, выявляется выраженная кривошея вследствие развития глазного тортиколлиса и положительный тест Бильшовского [2][3][4][5].…”
Section: Ophthalmology In Russia 2018;15(2s):106-112unclassified